Generational effect on nurses' work values, engagement, and satisfaction in an acute hospital - Si Hui Evangeline Tan; Guey Fong Chin (BMC, 2023)
Abstract Background The present nursing workforce comprises four generational of nurses working side-by-side. While such a generation blend adds invaluable diversity to the workforce, it also brings added complexity. The study aimed to describe and summarise work values and attitudes of four nursing generations, namely Baby boomers, Generation X, Y and Z. Method A cross-sectional questionnaire study was adopted. A total of 778 nurses from an acute hospital in Singapore completed the online questionnaire. The Work Value and Attitude scale measuring seven constructs (Work Centrality, Non-compliance, Technology Challenge, Work life balance, leadership, Power, and Recognition) was employed for data collection. Results The Cronbach's alpha was 0.714 for the overall instrument. Statistically significant differences amongst the four generations of nurses emerged in the Work Value and Attitude scale in the construct of non-compliance (p = 0.007), technology challenge (p = 0.027), work-life balance (p < 0.001), and recognition (p < 0.001). No statistically significant differences were noted for the rest of the constructs. Discussion and conclusion The findings of this study highlight that differences in work values and attitudes exist among nurses of different generations. Generation X are less likely to challenge the conventional norm and supervisors. Generation Y and Z are the most tech-savvy generations and can adapt quickly to new technology. There is also a greater emphasis on work-life balance as the generation gets younger. Generation Y and Z nurses perceived that younger nurses do not get due respect and recognition from their colleagues. Acknowledging the generational differences in work values and attitudes can facilitate nursing management to tailor strategies to improve individual and organisation performance while creating a work environment that enhances intergeneration harmony and teamwork.